Catalytic (de)hydrogenation promoted by non-precious metals - Co, Fe and Mn: recent advances in an emerging field - Filonenko, Georgy A; van Putten, Robbert; Hensen, Emiel J M; Pidko, Evgeny A (Chemical Society reviews, 2018)
Catalytic hydrogenation and dehydrogenation reactions form the core of the modern chemical industry. This vast class of reactions is found in any part of chemical synthesis starting from the milligram-scale exploratory organic chemistry to the multi-ton base chemicals production. Noble metal catalysis has long been the key driving force in enabling these transformations with carbonyl substrates and their nitrogen-containing counterparts. This review is aimed at introducing the reader to the remarkable progress made in the last three years in the development of base metal catalysts for hydrogenations and dehydrogenative transformations.